Stakeholder Interaction in the Development of Oxygen Ecotourism on Gili Iyang Island, Indonesia - Moh Musleh; Agus Subianto; Viv Djanat Prasita (Universitas Muhammadiyah Tangerang, 2023)
Oxygen Ecotourism on Gili Iyang Island has the highest oxygen levels reaching 21.5% above the normal threshold, the highest compared to other regions in Indonesia. This article adopts the collaborative viewpoint of the Quintuple Helix model, to discuss stakeholder interactions and highlight the level of success and identify several problems in the development of oxygen ecotourism on Gili Iyang Island, Sumenep Regency. This qualitative research uses a case study approach and visualizes collective interactions between stakeholders through the following five subsystems: 1) Education system, 2) Economic system, 3) Political system, 4) Media-based and culture-based society, 5) and Natural environment, Natural Environment Society based on the Quintuple Helix model from Carayannis and Campbell (2010). Data collection was carried out through observation, semi-structured interviews, and document review. The research results show that the Political System contributes to the initiation of ecotourism stakeholder collaboration, while an important role in the development of ecotourism has been played by the Higher Education System, as well as media-based and culture-based Societies. However, this collaboration is not yet optimal because it is still informal, and the lack of innovation from the Economic System, as well as the Natural Environment, and the Natural Environment of Society, is still limited. The findings of this research recommend that the role of local government (political system) needs to be increased by developing policies that ensure the maintenance of oxygen levels, increasing innovation in the use of local natural resources to support tourism, and institutionalizing stakeholder collaboration to ensure sustainable collaboration.Ekowisata Oksigen di Pulau Gili Iyang memiliki kadar oksigen tertinggi mencapai 21,5% di atas ambang batas normal, tertinggi dibandingkan wilayah lain di Indonesia. Artikel ini mengadopsi sudut pandang kolaborasi model Quintuple Helix, untuk membahas interaksi pemangku kepentingan dan menyoroti tingkat keberhasilan serta mengidentifikasi beberapa masalah dalam pengembangan ekowisata oksigen di Pulau Gili Iyang, Kabupaten Sumenep. Penelitian kualitatif ini menggunakan pendekatan studi kasus dan memvisualisasikan interaksi kolektif antara stakholder melalui lima subsistem berikut: 1) Sistem pendidikan, 2) Sistem ekonomi, 3) Sistem politik, 4) Masyarakat berbasis media dan berbasis budaya, 5) dan Lingkungan alam, Lingkungan Alam Masyarakat berdasarkan model Quintuple Helix dari Â Carayannis dan Campbell (2010). Pengumpulan data dilakukan melalui observasi, wawancara semi terstruktur, dan telaah dokumen. Hasil penelitian menunjukkan bahwa Sistem Politik berkontribusi pada inisiasi kolaborasi pemangku kepentingan ekowisata, sementara peran penting dalam pengembangan ekowisata telah dimainkan oleh Sistem Pendidikan Tinggi, serta Masyarakat berbasis media dan berbasis budaya. Namun kolaborasi tersebut belum optimal karena masih bersifat informal, serta kurangnya inovasi dari Sistem Ekonomi, maupun Lingkungan Alam, dan Lingkungan Alam Masyarakat masih terbatas. Temuan penelitian ini merekomendasikan bahwa peran pemerintah daerah (Sistem politik) perlu ditingkatkan dengan mengembangkan kebijakan yang menjamin pemeliharaan kadar oksigen, meningkatkan inovasi dalam pemanfaatan sumber daya alam lokal untuk mendukung pariwisata, dan melembagakan kolaborasi pemangku kepentingan untuk memastikan kolaborasi yang berkelanjutan.